2019
DOI: 10.1249/mss.0000000000001834
|View full text |Cite
|
Sign up to set email alerts
|

Gait Mechanics and T1ρ MRI of Tibiofemoral Cartilage 6 Months after ACL Reconstruction

Abstract: Purpose Aberrant walking biomechanics after anterior cruciate ligament reconstruction (ACLR) are hypothesized to be associated with deleterious changes in knee cartilage. T1ρ magnetic resonance imaging (MRI) is sensitive to decreased proteoglycan density of cartilage. Our purpose was to determine associations between T1ρ MRI interlimb ratios (ILR) and walking biomechanics 6 months after ACLR. Methods Walking biomechanics (peak vertical ground reaction f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 35 publications
2
109
0
Order By: Relevance
“…The lack of relationship between ultrasound and arthroscopy when assessing the lateral femur may be owing to different locations of cartilage being assessed by the two techniques. Since there are region-specific changes in cartilage composition after ACL injury that may be owing to alterations in location-specific joint loading throughout the knee ( Chen et al 2018 ; Pfeiffer et al 2019 ), further work is needed to ensure similar locations in comparing ultrasound and other examination methods ( e.g., MR imaging), to confirm that the same cartilage is being evaluated between techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of relationship between ultrasound and arthroscopy when assessing the lateral femur may be owing to different locations of cartilage being assessed by the two techniques. Since there are region-specific changes in cartilage composition after ACL injury that may be owing to alterations in location-specific joint loading throughout the knee ( Chen et al 2018 ; Pfeiffer et al 2019 ), further work is needed to ensure similar locations in comparing ultrasound and other examination methods ( e.g., MR imaging), to confirm that the same cartilage is being evaluated between techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, walking more slowly, coupled with other associated biomechanical changes, may contribute to the pathogenesis of patellofemoral OA by changing the direction, magnitude, and duration of forces (thereby also altering pressure) acting on the patellofemoral articular cartilage . Given that lower medial tibiofemoral joint contact forces are associated with tibiofemoral OA after ACLR, it is not surprising that slower walking speeds and, to a lesser degree, reduced knee excursions and lower quadriceps muscle forces—which collectively cause lower patellofemoral joint contact forces—were related to femoral trochlear cartilage degradation after ACLR. Cartilage responds to cyclic loading and may need an appropriate loading stimulus to maintain homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies investigating the association between walking mechanics and post‐traumatic OA, however, have examined the tibiofemoral joint, rather than the patellofemoral joint. These studies have found that unloading the tibiofemoral joint, especially its medial compartment, early after ACLR is associated with future tibiofemoral OA . One study by Culvenor et al found that those with established, radiographic patellofemoral OA approximately 9 years after ACLR walked with altered mechanics at that time.…”
mentioning
confidence: 99%
“…Animal models suggest that higher loading rates disrupt cartilage structure and biosynthesis . However, recent data in humans indicate that lower loading rates during walking 6 months post‐ACLR are associated with altered tibiofemoral cartilage composition (i.e., lower proteoglycan density) and metabolism . Future research is necessary to determine the influence of loading rate on knee joint health following ACLR.…”
Section: Discussionmentioning
confidence: 99%